Multiple response optimisation of the aqueous extraction of high quality ulvan from Ulva ohnoi. (September 2019) - Glasson, Christopher R.K.; Donnet, Luke; Angell, Alex; Vucko, Matthew J.; Lorbeer, Andrew J.; Vamvounis, George; de Nys, Rocky; Magnusson, Marie
Abstract: Response surface methodology was used to determine the effects of the solvent pH, the temperature of extraction, and the duration of extraction on the yield, purity, molecular weight, viscosity, and total metal content of ulvan extracted from U . ohnoi . Quadratic models identified the optimised responses for yield (72.6%) purity (68.2% w /w), molecular weight (92.9 kDa), viscosity (491.1 s), and total metal content (~0 mg/kg). These responses occurred between a solvent pH of 2.2–4.0, an extraction temperature of 61.3–90.0 °C, and an extraction duration of 55.0–90.0 min. The overall desirability of the ulvan product was determined using a Derringer's desirability function, which identified a solvent pH of 2.92, an extraction temperature of 90 °C, and an extraction duration of 90 min. These extraction conditions minimise the requirement for downstream purification and are suitable for upscaling the extraction of a high quality ulvan product. Graphical abstract: Unlabelled Image Highlights: Optimisation of the acid extraction of ulvan for product yield and quality pH selectivity for ulvan over contaminants limits downstream purification. Heavy metals within provisional tolerable monthly intake for human consumption Biorefinery process suitable for upscaling the production of a high quality ulvan